Regulatory Affairs in the Pharmaceutical Industry - Ali, Javed; Baboota, Sanjula (Elsevier Science & Technology, 2021)
Regulatory Affairs in the Pharmaceutical Industry is a comprehensive reference that compiles all the information available pertaining to regulatory procedures currently followed by the pharmaceutical industry.